Polygenic hazard scores in preclinical Alzheimer's disease - TAN, Chin Hong (Institutional Knowledge at Singapore Management University, 2017)
Identifying asymptomatic older individuals at elevated risk for developing Alzheimer's disease (AD) is of clinical importance. Among 1,081 asymptomatic older adults, a recently validated polygenic hazard score (PHS) significantly predicted time to AD dementia and steeper longitudinal cognitive decline, even after controlling for APOE e4 carrier status. Older individuals in the highest PHS percentiles showed the highest AD incidence rates. PHS predicted longitudinal clinical decline among older individuals with moderate to high CERAD (amyloid) and Braak (tau) scores at autopsy, even among APOE e4 non-carriers. Beyond APOE, PHS may help identify asymptomatic individuals at highest risk for developing Alzheimer's neurodegeneration.